Restricting Negligent Wastage / Pilferage at sites for Infrastructure Projects - Ganguly, Soumik (Digital Repository of Theses, 2025)
Indian topography offers various challenges in building infrastructure as it has different and adverse terrains, starting from plains to mountains and coastal belts. Investment in Indian infrastructure sector is a whopping 35percent of GDP. Across construction sites I have observed that, negligent wastage or pilferage of construction raw materials vary from 7 to 25 percent or even higher. Therefore, in this current competitive industry, it is imperative to restrict this wastage cost to a bare minimum otherwise survival of the institution would be at stake. There is no structured and generalized model till date in India that can be adopted by small and medium enterprises at a competitive price. So, to help them minimize this negligent wastage /pilferage it is imperative to make a model which would be productive for small and medium enterprises. Larger enterprises have gone for models that suit their business styles but those are not widely popular for their complexity and definitive use for the individual company, neither the smaller enterprises can afford the manpower and expenses required to run such a program. This wastage for mid-level and smaller companies can be controlled by the implementation of a model framework that requires easy to manage data points and proper intervention if the alerts are raised. The framework will ensure that the data points can be easily entered by site advisors in remote locations who have very less technological adoption or construction education. The aim of the study is to specifically restrict negligent wastage/ pilferage of construction materials at Project Site and to identify and build an intervention framework that helps in reducing the spillage. So, we intend to collect data across small and medium enterprises in a model state like West Bengal which has all the potential terrains through a frame of questionnaire to understand the industry-wide practices across unstructured small and medium enterprises in Eastern India to reduce this negligent wastage and draw a generic model to be applied across sites of construction to benefit the industry.